Swasembada Kedelai: antara Harapan dan Kenyataan (Forum Penelitian Agro Ekonomi, 2016)
In Indonesia, soybean is the third important food crop after rice and corn. After being success in achieving rice self-sufficiency, the goverment of Indonesia is trying to achieve self-suuficiency in other food crops like corn and soybean. Many efforts were done, including introduction of new varieties, special intensification (Gersus and Opsus), credit on palawija,and price policy, in order to encourage farmers to produce more soybean. This article is trying to show the performance of soybean self-sufficiency during the period of 25 years (1969-93) , and the future prospect of achieving self-sufficiency. The result of this study shows that since 1975 Indonesia fails to achieve self-sufficiency in soybean. This is due to the fact that the improvement of technology in soybean cultural practice is relatively slow compared to that of rice. The slow progress of technology in combination with the slow process of transfer of technology from reseach institutes to farmers have resulted in a low yield. From 1988 to 1994 the yield was stagnant at about 1.1 tons/ha in average. Another constraint to achieve soybean self-sufficiency is the fact that soybean is a temperate crop. In Indonesia, it gives a better yield in the high altitude areas. On the other hands, soybean in high altitude is less competitived compared to horticulture crops, esspecialy vegetables. Therefore, special efforts are needed, esspecialy the utilization of bio-technology in plant breeding program of soybean in order to accelerate the achievement of soybean self sufficiency in the future